Correlation between numerical interpretation and analysis abilities with critical analysis ability on biology education students - M. Arsyad (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2023)
Numerical literacy and critical thinking skills are important 21st-century competencies for prospective biology teacher students in South Kalimantan. Some of these competencies include interpreting and analysis numeracy as well as critical analysis abilities. This study aims to analyze the correlation between Numerical interpretation and analysis ability with critical analysis ability of students' education biology. This study is quantitative correlational research. The sample of this research was 245 biology education students in South Kalimantan from Lambung Mangkurat University, UIN Antasari Banjarmasin, and STKIP PGRI Banjarmasin. Test instruments Numerical interpretation and analysis abilities refer to AACU, and critical analysis ability test instrument developed refer to Facione with the types of multiple choice questions and each variable totaling 6 (six) questions. Test instrument has been validated by empirical validation using a correlation test. The type of data collected is quantitative data from the scoring results of the three variables that are measured and analyzed using the Pearson Product Moment correlation test and multiple correlation tests with SPSS 26. Results of the study show a significant correlation between ability numerical interpretation ability with critical analysis ability, and other relationships also exist in numerical analysis ability with critical analysis ability in Biology Education Students.Abstrak Literasi numerasi dan kemampuan berpikir kritis merupakan kompetensi abad 21 yang penting dimiliki oleh mahasiswa calon guru biologi di Kalimantan Selatan. Beberapa kompetensi tersebut diantaranya adalah kemampuan interpretasi dan analisis numerasi serta kemampuan analisis kritis. Penelitian ini bertujuan untuk menganalisis hubungan antara kemampuan interpretasi dan analisis numerasi dengan kemampuan analisis kritis mahasiswa pendidikan biologi di Kalimantan Selatan. Jenis penelitian ini adalah penelitian kuantitatif korelasional. Sampel penelitian ini yaitu mahasiswa Pendidikan Biologi di Kalimantan Selatan berjumlah 245 orang dari Universitas Lambung Mangkurat, UIN Antasari, dan STKIP PGRI Banjarmasin. Instrumen tes kemampuan interpretasi dan analisis numerasi merujuk pada AACU dan Instrumen tes kemampuan analisis kritis dikembangkan dengan merujuk pada Facione dengan jenis soal pilihan ganda dan masing-masing variabel berjumlah 6 (enam) soal. Instrumen tes divalidasi dengan validasi empiris menggunakan uji korelasi. Jenis data yang dikumpulkan merupakan data kuantitatif dari hasil penskoran ketiga variabel yang diukur dan dianalisis dengan menggunakan uji korelasi Pearson Product Moment dan uji korelasi berganda dengan SPSS 26. Hasil analisis menunjukkan adanya hubungan yang signifikan secara simultan antara Kemampuan Interpretasi dan Analisis Numerasi dengan Kemampuan Analisis Kritis Mahasiswa Pendidikan biologi di Kalimantan Selatan.